PENERIMAAN DIRI REMAJA CEREBRAL PALSY - FITRIA LISTIANI (Character Jurnal Penelitian Psikologi, 2015)
Abstrak Tujuan dari penelitian ini adalah untuk mengetahui gambaran penerimaan diri dan faktor-faktor yang mempengaruhi penerimaan diri remaja cerebral palsy. Penelitian ini menggunakan pendekatan kualitatif dengan menggunakan metode studi kasus. Subjek dalam penelitian ini berjumlah 3 remaja CP dengan masing-masing 2 significant others. Pengumpulan data yang digunakan dalam penelitian ini adalah wawancara. Metode analisis data yang digunakan adalah analisis tematik. Hasil penelitian menunjukkan bahwa ditemukan dua tema besar yaitu gambaran penerimaan diri dan faktor-faktor yang mempengaruhi penerimaan diri remaja CP. Mengetahui kelainan yang dimiliki, merasa memiliki kelebihan, penyesuaian diri terhadap kondisi CP, penyesuaian diri dengan lingkungan sosial, kebutuhan-kebutuhan remaja CP, dan mempunyai pandangan masa depan merupakan gambaran penerimaan diri remaja CP. Faktor-faktor yang mempengaruhi penerimaan diri remaja cerebral palsy antara lain, menjalin hubungan baik dengan orang lain, adanya dukungan sosial (keluarga, guru, dan teman) dan sikap positif. Hasil penelitian telah menemukan sikap penerimaan diri pada remaja CP memberikan dampak positif antar lain, perasaan semangat tidak putus asa, mandiri, percaya diri, bertanggungjawab, dan mempunyai tujuan hidup. Kata kunci : Remaja Cerebral Palsy, Penerimaan Diri. Abstract Cerebral palsy known as CP, is a movement disruption and body posture caused by damage in the brain area that controls motoric function. Brain damage that causes cerebral palsy can occur before, during, or shortly after birth. For some adolescents with physical disabilities (cerebral palsy), growing as a teenager will face some specific challenges. Besides, facing difficulties in motor function, adolescents are also trying to accept their physical condition. The objective of this study is to know the description of self-acceptance and the factors that affect self acceptance of adolescent with cerebral palsy. The research used a qualitative approach using case studies. The subjects in this study were 3 teenagers with CP with each 2 significant others. The data collection used in this study were interviews. Data analysis method used was thematic analysis. The result found two big themes that are an overview of self-acceptance and the factors that affect self-acceptance of adolescent with CP. That are understanding to the abnormalities suffered, understanding to self-potentials or abilities, adjustment to CP condition, adjustment to the social environment, the needs of adolescents with CP, abilitas to having an optimistic view of the future. Factors that affect self-acceptance of adolescent with cerebral palsy that are, establish good relationships with others, the existence of social support (family, teachers, and friends) and a positive attitude. The results of this study found that behavior of self-acceptance in adolescent with cerebral palsy contributes to positive impacts that are the feeling of optimism, independent, self-confidence, responsible, and having life purpose. Keywords: Adolescent Cerebral Palsy, Self-Acceptance.